Ante-, peri- and postnatal factors associated with intraventricular hemorrhage in very premature infants. (January 2018) - Poryo, Martin; Boeckh, Judith Caroline; Gortner, Ludwig; Zemlin, Michael; Duppré, Perrine; Ebrahimi-Fakhari, Daniel; Wagenpfeil, Stefan; Heckmann, Matthias; Mildenberger, Eva; Hilgendorff, Anne; Flemmer, Andreas W.; Frey, Georg; et al.
Abstract: Background: Intraventricular hemorrhage (IVH) is one of the most serious complications in preterm infants and is associated with neurological sequelae and mortality. Over the past few decades, the rate of IVH has decreased due to improved neonatal intensive care. However, up to 15–25% of very and extremely premature infants (< 32 and < 28 weeks of pregnancy (WOP) respectively) still suffer from IVH. Study purpose. The aim of this study was to perform an updated, multicenter analysis to identify ante-, peri, and postnatal factors other than gestational age/birth weight associated with IVH of any grade in a large cohort of very and extremely premature infants. Methods: We performed a retrospective analysis in a prospectively conducted multicenter cohort study between 01/01/1998–31/12/2012 at 5 level 3 perinatal centers. All relevant ante-, peri- and neonatal data were collected and univariate as well as multivariate logistic regression analysis was performed. Results: 765 inborn infants with a gestational age < 32 WOP were enrolled into this study (369 (48.2%) female; 396 (51.8%) male). Birth weight ranged from 315 g to 2200 g (mean 1149.7 g, SD 371.9 g); 279 (36.5%) were born ≤ 27 + 6 WOP and 486 (63.5%) ≥ 28 + 0 WOP. IVH was seen in 177 (23.1%) patients. Multivariate analysis revealed that in addition to higher gestational age (OR 0.7, CI [0.6–0.8]), antenatal steroid treatment (OR 0.3, CI [0.2–0.6]) and caesarian section without uterine contraction (OR 0.6, CI [0.4–0.9]) were associated with a lower rate of IVH while RDS (OR 5.6, CI [1.3–24.2]), pneumothorax (OR 2.8, CI [1.4–5.5]) and use of catecholamines (OR 2.7, CI [1.7–4.5]) were associated with an increased risk of IVH. After exclusion of gestational age and birth weight from multivariate analysis, early onset sepsis (OR 1.6, CI [1.01–2.7]) and patent ductus arteriosus (OR 1.9, CI [1.1–3.1]) were associated with a higher rate of IVH. In addition, univariate analysis revealed that Apgar scores at 5 min ( p  < 0.001), BDP/ROP/NEC (p < 0.001), mechanical ventilation ( p  < 0.001) and inhalative nitric oxide (p < 0.001) were significantly associated with IVH. Conclusions: Our comprehensive analysis demonstrated that the occurrence of IVH in very premature infants is significantly associated with ante-, peri- and postnatal factors being either related to the degree of immaturity or indicating a critical clinical course after birth. The analysis reiterates the necessity for a very close cooperation between obstetricians and neonatologists to reduce the incidence of IVH in this susceptible cohort. Highlights: Higher GA, ANS and caesarian section prior to onset of labor were associated with a lower rate of IVH while RDS, pneumothorax and catecholamines with an increased risk of IVH (multivariate analysis). After exclusion of GA/birth weight from multivariate analysis, EOS and PDA were significantly associated with a higher rate of IVH. Apgar scores at 5 minutes, BDP/ROP/NEC, mechanical ventilation and inhalative nitric oxide were significantly associated with IVH (univariate analysis) To reduce the incidence of IVH in this cohort a very close cooperation between obstetricians and neonatologists is mandatory.